2003
DOI: 10.1111/j.1834-7819.2003.tb00005.x
|View full text |Cite
|
Sign up to set email alerts
|

Social and behavioural determinants of early childhood caries

Abstract: Background: To investigate the association between selected social and behavioural (infant feeding and preventive dental practices) variables and the presence of early childhood caries in preschool children within the north Brisbane region. Methods: A cross sectional sample of 2515 children aged four to five years were examined in a preschool setting using prevalence (percentage with caries) and severity (dmft) indices. A self-administered questionnaire obtained information regarding selected social and behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
144
8
17

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(183 citation statements)
references
References 19 publications
14
144
8
17
Order By: Relevance
“…Most of children have started brushing at age 1 (50.7%) and 45.3% started at 2nd year and only 4% at 6 months. These finding are in agreement with the study conducted on Australian children [11] Night time bottle feeding with juice, repeated use of a no spill cup and frequent consumption of sugar in between meals containing snacks or drinks increases the risk of caries.…”
Section: Discussion:-supporting
confidence: 82%
“…Most of children have started brushing at age 1 (50.7%) and 45.3% started at 2nd year and only 4% at 6 months. These finding are in agreement with the study conducted on Australian children [11] Night time bottle feeding with juice, repeated use of a no spill cup and frequent consumption of sugar in between meals containing snacks or drinks increases the risk of caries.…”
Section: Discussion:-supporting
confidence: 82%
“…There is a close relationship between health level and cultural and socioeconomic disadvantage, and it was observed that caries affects mainly children from families of less favored social classes, with lower education level and greater difficulty in accessing education in health care (7)(8)(9) . To prevent the development of caries in infants, there is a need to implement programs aimed at promoting health in early childhood (6) , because it was demonstrated that there was an important decrease in caries incidence among groups of children benefited from preventive programs (10)(11)(12)(13) .…”
Section: Introductionmentioning
confidence: 99%
“…A diversidade de resultados talvez se deva à idade dos sujeitos, a diferenças metodológicas, mas, principalmente, a ações preventivas e de planejamento de ações odontológicas muito diversas nas cidades em que se realizaram as pesquisas. Em Paulínia 9 e em outras cidades do interior paulista 46 ocorrem levantamentos epidemiológicos de rotina para diagnosticar as condições de saúde bucal das populações, contribuindo para um planejamento mais direcionado dos serviços de saúde 9,47 , assim como há monitoramento contínuo das condições bucais das crianças. Segundo Baldani et al 48 , para facilitar o monitoramento e a adesão aos programas de atenção em saúde bucal, tanto curativos, preventivos como educativos, eles precisam ocorrer em contextos que atendam crianças pequenas, como na Estratégia de Saúde da Família -ESF, nos centros de saúde, onde vão para as consultas de Puericultura e nas creches e pré-escolas.…”
Section: Discussionunclassified